2021
DOI: 10.2196/27589
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Mobile Platform for Real-world Digital Measurement of Depression: User-Centered Design, Data Quality, and Behavioral and Clinical Modeling

Abstract: Background Although effective mental health treatments exist, the ability to match individuals to optimal treatments is poor, and timely assessment of response is difficult. One reason for these challenges is the lack of objective measurement of psychiatric symptoms. Sensors and active tasks recorded by smartphones provide a low-burden, low-cost, and scalable way to capture real-world data from patients that could augment clinical decision-making and move the field of mental health closer to measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 19 publications
6
49
0
Order By: Relevance
“…In another large study of 288 participants studying mood and anxiety, Meyerhoff et al 6 employed a different approach, looking at correlations between changes in weekly survey scores and changes in passive data features. Focusing on GPS, call, text and app usage features, this study also reported low correlations similar to Nickels et al 5 Meyerhoff et al also separated participants into groups, using k -means clustering on the participants’ clinical scores, and found that some correlations were higher in groups exhibiting symptoms. 6 In this work, we aim to explore correlations in a large data-set collected with the mindLAMP app from college student participants, to assess if we observe correlations of a similar magnitude to Nickels et al 5 and Meyerhoff et al 6 In addition, we explore whether changing the group of participants that we use for analysis (such as by setting data-quality thresholds or by splitting into clinical groups) will allow us to identify more clinically meaningful correlations.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…In another large study of 288 participants studying mood and anxiety, Meyerhoff et al 6 employed a different approach, looking at correlations between changes in weekly survey scores and changes in passive data features. Focusing on GPS, call, text and app usage features, this study also reported low correlations similar to Nickels et al 5 Meyerhoff et al also separated participants into groups, using k -means clustering on the participants’ clinical scores, and found that some correlations were higher in groups exhibiting symptoms. 6 In this work, we aim to explore correlations in a large data-set collected with the mindLAMP app from college student participants, to assess if we observe correlations of a similar magnitude to Nickels et al 5 and Meyerhoff et al 6 In addition, we explore whether changing the group of participants that we use for analysis (such as by setting data-quality thresholds or by splitting into clinical groups) will allow us to identify more clinically meaningful correlations.…”
supporting
confidence: 80%
“…Focusing on GPS, call, text and app usage features, this study also reported low correlations similar to Nickels et al 5 Meyerhoff et al also separated participants into groups, using k -means clustering on the participants’ clinical scores, and found that some correlations were higher in groups exhibiting symptoms. 6 In this work, we aim to explore correlations in a large data-set collected with the mindLAMP app from college student participants, to assess if we observe correlations of a similar magnitude to Nickels et al 5 and Meyerhoff et al 6 In addition, we explore whether changing the group of participants that we use for analysis (such as by setting data-quality thresholds or by splitting into clinical groups) will allow us to identify more clinically meaningful correlations. Finally, we aim to test a classifier for predicting survey scores with passive and survey data, to assess whether passive data signals alone are enough to build predictive models or if survey data is necessary to provide a stronger signal.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Our results are in line with those derived from more traditional methods. For example a recent paper from Verily 10 found that smartphone mobility metrics were also correlated with mood. Contrarily, another paper 11 with a sample of 255 participants found that there were no significant associations between changes in symptom severity measures and subsequent changes in sensor-derived behavioral features.…”
Section: Discussionmentioning
confidence: 99%